A study of therapeutic effects of 670 nm irradiation in different types of diabetic macular edema - S. Ramin; M. Ahadi; A. Ebrahimi (Biomedical Photonics)
The purpose of this study was to investigate the therapeutic effects of 670 nm irradiation in patients with diabetic macular edema. In several studies, positive effects of red/near-infrared irradiation showed in a range of ocular diseases such as macular degeneration, macular edema, and retinitis pigmentosa. This study was conducted on forty five eyes of 26 diabetic patients with macular edema between the ages of 51 and 80.Measurement of visual acuity and slit lamp examination, funduscopy, and optical coherence tomography were performed in all subjects. None of the patients had proliferative retinopathy. We used a portable LED device (Warp 10, Quantum Devices) for treatment. Patients held this device at a distance of 3 cm from their eyes for 240 seconds for three months. Full ophthalmic examinations were repeated 1, 2, and 3 months after treatment.After 3 months, the mean visual acuity improved from 0.44 ± 0.38 log MAR to 0.27 ± 0.24 log MAR and vision increased by 1.52 ± 1.16 lines post treatment (р<0.001). The mean central macula thickness decreased from 381.49 ± 144.40 μm to 359.72 ± 128.84 μm (р=0.050). In patients with mild and moderate nonproliferative diabetic retinopathy, the mean central retinal thickness decreased 52.06 ± 67.78 μm and 39.27 ± 44.69 μm, respectively, but patients with severe type showed an increase of 34.93 ± 65.65 μm in the mean central retinal thickness (р<0.001). Also, the severity of macular edema had no effect on final outcomes (р>0.05). Photobiomodulation can positively affect diabetic macular edema, especially in patients with mild to moderate diabetic retinopathy.